DEVELOPING A BILINGUAL BOOK “PONTIANAK CITY HIGHLIGHT” FOR AN EXTENSIVE READING PROGRAM - Stella Prancisca (STKIP Persada Khatulistiwa Sintang, 2021)
Reading is often perceived as a key activity for helping students learn a new language, not only in the first language but also in the foreign language. Unfortunately, some surveys report that Indonesian people have a low reading habit. Thus, this research develops a reading book which is visually interesting, easy in level, and not too long. The research followed the extensive reading framework as it was said capable of maintaining student’s motivation in reading. This research also adopted bilingualism principles and was packed with local-related topics such as tourism destinations in Pontianak City. ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was chosen as the main methodology because it was believed as the most popular and has been used extensively in R&D research. However, due to time and word count limitations, the current paper only discusses the first three steps of the ADDIE model. Results of the research confirmed earlier reports having documented the participant’s low level of reading motivation. Such a claim was derived from data related to the reading duration and the quantity of books that the students read. Besides, their English competence was also lacking, so a bilingual book might be preferred. The students also revealed that they barely found an English language book containing local culture information. This information then became a starting point for the researcher in designing the reading book. The information allowed the researcher to determine the book content, the vocabulary levels, the length, and its visual appearance.